Integritas Seorang Auditor Internal Pemerintah : Telaah Konseptual Berdasarkan Perspektif al-Qur'an - Nandyasa Vania Sarinastiti; Erina Sudaryati (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
This study examines the concept of integrity of government internal auditors from the perspective of the Qur'an with a hermeneutic approach. The Qur'an provides a strong moral foundation in instilling integrity, which includes honesty, responsibility, and accountability. In the context of the auditor profession, integrity serves as the main guideline to ensure transparency and fairness in the performance of duties. This study found that Islamic values contained in the Qur'an, such as honesty in QS. Al-Baqarah: 42, fulfillment of trust in QS. An-Nisa: 58, and justice in QS. Al-Ma'idah: 8, are relevant to strengthen the professional ethics of auditors. This research is expected to contribute to the development of an auditor code of ethics based on Islamic religiosity values to support clean and transparent governance. Keywords: Integrity, Government Internal Auditor, Al-Qur'an, Honesty, Ethics